Dichotomy in Neutralizing Antibody Induction to Peptide-Conjugated Vaccine in Squalene Emulsion Contrast With Aluminum Hydroxide Formulation - Bonduelle, Olivia; Chaudesaigues, Chloé; Tolazzi, Monica; Suleiman, Ehsan; de Bernard, Simon; Alves, Karine; Nourikyan, Julien; Bohec, Mylene; Baudrin, Laura G.; Katinger, Dietmar; Debré, Patrice; Scarlatti, Gabriella; et al. (Frontiers in Immunology, 2022)
W614A-3S peptide is a modified 3S motif of the HIV-gp41 (mutation W614A). We previously detected the presence of natural neutralizing antibodies directed against W614A-3S peptide (NAbs) in long-term non-progressor HIV+ patients. Here, we compared the efficacy of W614A-3S peptide formulated in either squalene emulsion (SQE) or in aluminum hydroxide (Alum) in inducing broadly-NAbs (bNAbs). Rabbit and mouse models were used to screen the induction of bNAbs following 4 immunizations. SQE was more efficient than Alum formulation in inducing W614A-3S-specific bNAbs with up to 67-93% of HIV strains neutralized. We then analyzed the quality of peptide-specific murine B cells by single-cell gene expression by quantitative Reverse Transcription-PCR and single-cell V(D)J sequencing. We found more frequent germinal center B cells in SQE than in Alum, albeit with a different gene expression profile. The V(D)J sequencing of W614A-3S-specific BCR showed significant differences in BCR sequences and validates the dichotomy between adjuvant formulations. All sixteen BCR sequences which were cloned were specific of peptide. Adjuvant formulations of W614A-3Speptide-conjugated immunogen impact the quantity and quality of B cell immune responses at both the gene expression level and BCR sequence.